Sex Disparities in Gallstone Disease: Insights from the Mauco Prospective Population-Based Cohort Study - Vargas-Rona, C (BMJ Publishing Group, 2024)
Objective To investigate factors associated with the prevalence and incidence of gallstone disease (GSD) in women and men of the MAUCO population-based prospective cohort. Design 8948 MAUCO participants (aged 38-74 years) underwent abdominal ultrasound at baseline (2015-2019); 4385 received follow-up ultrasound at years 2 or 4. Factors associated with prevalent GSD were assessed using Poisson multiple regression and with incident GSD using Cox regression models. Results GSD prevalence was 40.4% in women (13.1% gallstones, 27.3% cholecystectomies) and 17.1% in men (8.9% gallstones, 8.2% cholecystectomies). In men, GSD prevalence rate ratio (PRR) by age in >64 years was 3.85 (95% CI 3.00 to 4.94), doubling that of women s PRR 1.78 (95% CI 1.57 to 2.01). In women, waist circumference and diabetes were stronger GSD factors; a higher number of children and worse metabolic and socioeconomic conditions were also highlighted. GSD men had higher cardiovascular disease and a family history of GSD and gallbladder cancer. 198 GSD cases developed during follow-up, with incidence increasing by 2% (95% CI 1.005% to 1.03%) per each centimetre above the ideal waist circumference, statistically significant only in women. In men, age was the strongest factor for incidence, followed by a family history of GSD and low high-density lipoprotein increased incidence risk. Conclusions GSD burden was high in this population; a third of women had their gallbladder removed, which may pose them at risk of other health problems. Abdominal obesity was the only preventable GSD risk factor, highlighting the need for effective public health policies promoting obesity reduction. © Author(s) (or their employer(s)) 2024.